Insectos del orden lepidoptera detectados en plantas de Noni (Morinda citrifolia L.) - Gonzalez Garcia, N.=700 1 Aviles Pacheco, R.; Cruz Diaz, B.; Martinez Suarez, Y.
(Es, En)
Ilus., 7 ref.
Keywords: MORINDA CITRIFOLIA; INSECTOS DAÑINOS; LEPIDOPTERA; INSECTOS DEPREDADORES DE LAS HOJAS; CUBA; NONI